Business Model Innovation: Lesson Learned From EV Ecosystem In Indonesia. Issue 1 (1st October 2022) - Amir, M T; Prabawani, B
Abstract: Although relatively developed in advanced countries, the electric vehicle (EV) industry in Indonesia is still in the early stages of development. Designing a business model with an ecosystem perspective is critical for relevant stakeholders because there are still many uncertainties to be faced, including the unclear structure of the industry. This study examines the case of how an e-bus company creates a business model by taking into account the important role of stakeholders in their ecosystem. Top management of a manufacturing company and its parent company were in-depth interviewed. The roles and critical challenges of regulators, battery manufacturers, and assembly plants are explored. The practice of creating business models will be compared with applying business models in the literature. The discussion will focus on the need of the focal company in creating value through approaching regulators, collaborating with battery manufacturer, and creating communication as the innovations. The findings in this study are expected to be input for e-bus business actors for sustaining the development stage and stakeholders in the existing ecosystem, including the government or regulators.